Organoselenium Compounds in Catalysis - Gallo-Rodriguez, Carola; Rodríguez, Juan B. (Synthesis, 2024)
In this article we have focused on the use of selenium in catalysis along with the proposed reaction mechanisms. With increasing interest in selenium chemistry, we have highlighted the most significant features of this subject, mainly in the last years. Selenium-containing catalysts have a key role in many transformations; for example, oxidation reactions that are performed under very mild and controlled conditions. In addition, utilizing the weak selenium–oxygen bonding interaction has proved to be very useful as a catalytic approach for specific transformations. The catalytic cycles of each appropriate transformation are fully reviewed.1 Introduction2 Use of Selenium in Catalysis: Perspectives2.1 Selenium as Directing Group: Preparation of Organoselenium Compounds via C–H Borylation2.2 Multicomponent Reactions Employing Selenium as a Catalyst2.3 Selenium-π-Acid Catalysts2.4 Electrochemical Selenium-Catalyzed Reactions2.5 Stereoselective Synthesis Employing Organoselenium Catalysts2.6 Transition-Metal Catalysts Containing Selenium-Based Ligands2.6.1 Selenium-Ligated Palladium(II) Complexes as Catalysts for the Heck Reaction2.6.2 Pincer Selenium Catalyst for the Allylation of Aldehydes and Closely Related Functional Groups2.6.3 Selenium Employed in Buchwald-Type C–N Coupling Reactions2.6.4 Organoselenium Catalysts in Suzuki–Miyaura Coupling Reactions2.7 Organoselenium Catalysis in Michael-Type Reactions2.8 Catalytic Cycle for Glutathione Peroxidase2.9 Epoxidation2.10 Dihydroxylation2.11 Oxidation2.12 Bromolactonization2.13 Preparation of Alkenes from Vicinal Diols2.14 Preparation of α-Selanyl Enals from Propargylic Alcohols2.15 Miscellanea3 Concluding Remarks
Keywords: selenium; catalysis; organocatalysis; pincer catalysts; glutathione peroxidase; oxidation